Different Calcium and Src Family Kinase Signaling in Mac-1 Dependent Phagocytosis and Extracellular Vesicle Generation - Lőrincz, Ákos M.; Szeifert, Viktória; Bartos, Balázs; Szombath, Dávid; Mócsai, Attila; Ligeti, Erzsébet (Frontiers in Immunology, 2019)
Encountering opsonized particles by neutrophils results in phagocytosis of the particle and generation of extracellular vesicles with antibacterial property (aEV). The aim of the present study is to compare the involvement of different receptors and receptor-proximal signaling pathways in these two parallel processes. Investigating human neutrophils from peripheral blood, we show that complement receptors are decisive for both processes whereas immunoglobulin binding Fc receptors (FcR) only participate moderately in phagocytosis and pattern recognition receptors induce mild EV production but only minimal phagocytosis. Studying bone marrow derived neutrophils of genetically modified animals we verify that the involved complement receptor is CR3, also known as the β2 integrin Mac-1. We show that genetic deletion of the adaptor molecules FcRγ chain or DAP12 does not influence either process, suggesting potential redundant function. Combined absence of the Src family kinases Hck, Fgr, and Lyn drastically impairs phagocytosis but does not influence aEV production. In contrast, deletion of PLCγ2 has no influence on phagocytosis, but reduces aEV formation. In accord with the essential role of PLCγ2, aEV biogenesis both from murine and from human neutrophils is dependent on presence of extracellular calcium. Absence of external calcium prevented the generation of antibacterial EVs, whereas the spontaneous EV formation was not influenced. We thus show that phagocytosis and biogenesis of antibacterial EVs are independent processes and proceed on different signaling pathways although the same receptor plays the critical role in both. Our data reveal the possibility in neutrophilic granulocytes to modulate aEV production without disturbing the phagocytic process.